PENERAPAN METODE BLENDED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MENULIS CERPEN PADA SISWA KELAS VII SMPN 7 DENPASAR - Maria Kristavera Burga; Dewa Gede Bambang Erawan; I Komang Widana Putra (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2023)
This reseach is classroom action research ( PTK) which aims to(1) test the eeffectiveness of the brainwriting method in blended learning the writing skil of ezposition test in class VII SMPN 7 Denpasar; (2) Knowing the steps of the branwriting metod the blended learning theb skill of writing method inexposition test in class VII student at smpn 7 Denpasar. Data collection was carried using observation tes an quantitative ang qualitative. The data that has been obtained was analized using a applying the brainwriting method there was an increase in the skils off writing exposition text in class VII student at SMPN 7 Denpasar. The improvement in writing skills off exposition text can be seen from the results of the student’savaerage scores obtained in the first cycle test, which wa 5,7% and increased ins the secos cycle, which was 8,18%. Step impleming the method carried out, namely: (1) preparing a lesson plan( RPP), as wll as preparing learning matrials an and explaining the material, (2) student are allowed to ask questions regarding the material being discussed an the teacher delivers words at can arouse enthusiasm an provide motivation for student (3) student will write free short strory text themes which will later be formet in a paragraf, ( 4) then stundet are allowed to discuss with the theme of bench to exchange ideas, both in the form of suggestion. The results of the application of the method were carried out well.